One-year assessment of physical activity level in adult Qatari females: a pedometer-based longitudinal study - Sayegh S; Van Der Walt M; Al-Kuwari MG (Dove Medical Press, 2016)
Suzan Sayegh, Mercia Van Der Walt, Mohamed Ghaith Al-Kuwari Exercise is Medicine Department, Aspetar Orthopedic and Sports Medicine Hospital, Doha, Qatar Background: Physical inactivity is a growing health concern and has been identified as the fourth leading risk factor for global mortality. The Arab region includes countries with some of the world’s highest physical inactivity levels, such as Qatar, more specifically the Qatari female population.Objective: The objective of this study is to assess the physical activity levels of Qatari national female adults during a 1-year pedometer-based program.Materials and methods: A total of 549 Qatari national females aged between 18 years and 64 years were included. Data extracted from “Step into Health” program web database in Qatar were used for analyses. Daily habitual physical activity (daily total step count and aerobic steps) was assessed through the Omron HJ-324U pedometer. Step counts were classified as follows: <5,000 steps/d, sedentary; 5,000–7,499 steps/d, low active; and ≥7,500 steps/d, physically active. Statistical significance was set at P-value ≤0.05. Descriptive statistics were used, and habitual physical activity was calculated through repeated measures analysis of variance to determine the difference across the monitored days.Results: Mean age was 37.4±11.7 years, and median body mass index of 28.8 kg/m2 (interquartile range 24.8–33.5). Daily steps for the overall population ranged from 3,505 steps/d to 10,010 steps/d, with a median of 6,008 steps/d. A total of 242 (44.1%) females were sedentary, 178 (32.4%) were low active, and 129 (23.5%) were physically active. The physically active group showed a median of 927 aerobic steps/d (interquartile range 0–4,248).Conclusion: Based on the results of this study, Qatari females are not meeting the global recommendations of physical activity. Future research might need to consider barriers to physical activity as well as social, cultural, and environmental factors. Keywords: aerobic steps, daily steps, step count, community-based program